2013
DOI: 10.1088/1475-7516/2013/10/021
|View full text |Cite
|
Sign up to set email alerts
|

Neutron stars in a perturbativef(R) gravity model with strong magnetic fields

Abstract: We investigate the effect of a strong magnetic field on the structure of neutron stars in a model with perturbative f (R) gravity. The effect of an interior strong magnetic field of about 10 17∼18 G on the equation of state is derived in the context of a quantum hadrodynamics (QHD) model. We solve the modified spherically symmetric hydrostatic equilibrium equations derived for a gravity model with f (R) = R + αR 2 .Effects of both the finite magnetic field and the modified gravity are detailed for various valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Some other authors, nevertheless, supported our work in their computations [17][18][19], In fact, Federbush et al [19], by an extensive mathematical analysis, have shown the existence of stable magnetic star solutions, which include our super-Chandrasekhar white dwarfs [10]. Nityananda and Konar [20] have raised exactly the same question as the earlier critics [15,16], but have only stated it more circuitously, contributing nothing new in our view.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Some other authors, nevertheless, supported our work in their computations [17][18][19], In fact, Federbush et al [19], by an extensive mathematical analysis, have shown the existence of stable magnetic star solutions, which include our super-Chandrasekhar white dwarfs [10]. Nityananda and Konar [20] have raised exactly the same question as the earlier critics [15,16], but have only stated it more circuitously, contributing nothing new in our view.…”
supporting
confidence: 72%
“…Some other authors, nevertheless, supported our work in their computations [17][18][19], In fact, Federbush et al [19], by an extensive mathematical analysis, have shown the existence of stable magnetic star solutions, which include our super-Chandrasekhar white dwarfs [10].…”
supporting
confidence: 67%
“…Whittenbury et al (2012), based on quark-meson coupling model, showed that the maximum mass of neutron stars could be ≈ 2M⊙, when nuclear matter is in β-equilibrium and hyperons must appear. Apart from the exploration based on the equation of state (EoS), as mentioned above, neutron stars with ⋆ sathynius2@gmail.com † bm@physics.iisc.ernet.in mass 2M⊙ were shown to be possible by exploring effects of magnetic fields, with central field Bc ∼ 10 16 G (Pili et al 2014;Sinha et al 2013), and modification to Einstein's gravity (Arapoglu et al 2014;Astashenok et al 2012;Cheoun et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Modification of gravity can affect a number of important physical characteristics of NSs which can, in principle, be directly verified observationally. Among them are the mass-radius (M − R) relation [16][17][18], the properties of electromagnetic radiation from the surface of accretion disks [19], and the structure of internal and external magnetic fields [20][21][22][23]. Considering such objects within the framework of different types of f (R) gravities and using various equations of state (EoSs) for neutron matter, one can reveal the allowed forms of f (R) and EoSs satisfying the observational constraints.…”
Section: Introductionmentioning
confidence: 99%